Neurologic Signs of Lyme Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Clinical manifestations of Lyme disease (LD) in 97 seropositive children were reviewed at the Children's Hospital of Philadelphia, with particular attention to neurologic symptoms and signs.